The right insula contributes to memory awareness in cognitively diverse older adults. (August 2015) - Cosentino, Stephanie; Brickman, Adam M.; Griffith, Erica; Habeck, Christian; Cines, Sarah; Farrell, Meagan; Shaked, Danielle; Huey, Edward D.; Briner, Tamara; Stern, Yaakov
Abstract: Unawareness of memory loss is a challenging characteristic of Alzheimer's disease (AD) and other age-related neurodegenerative conditions at their earliest stages, adversely affecting important outcomes such as patient decision making and safety. The basis of this metacognitive disturbance has been elusive; however it is almost certainly determined in part by compromise to brain regions critical for self-assessment. The subjectivity of traditional measurements of self-awareness in dementia has likely limited the rigor with which its neuroanatomic correlates can be established. Here we objectively measure memory awareness (metamemory) using a Feeling of Knowing (FOK) task in a group of cognitively diverse older adults, including 14 with mild AD and 20 cognitively healthy older adults. Performance on the metamemory task was examined in relation to the structural integrity of 14 bilateral neuroanatomic regions hypothesized to support self-awareness. Less accurate metamemory was associated only with reduced right insular volume ( r =.41, p =.019). Implications of the current findings for models of metacognitive aging are discussed, with attention to the role of the insula in the conscious detection of errors. Highlights: Disordered awareness of memory loss is a common feature of Alzheimer's disease. We examined the structural correlates of metamemory in cognitively diverse elders. Metamemory was associated with right insular volume. Disordered awareness of memory loss in AD may reflect impaired detection of errors.